SiGeSn material for integrated optical devices - Oehme, M.; Schwarz, Daniel; Clausen, C. J.; Fischer, I. A.; Schulze, J. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
In this paper, an ultra-thin buffer technology for the epitaxial growth of SixGe1-x-ySny structures on Si or Si-on-Insulator substrates by using molecular beam epitaxy is presented. This technology builds the basis for integrated photonic devices as detectors, modulators and light sources. The paper discusses different device families with different material compositions, which all use a relaxed Ge virtual substrate with high quality. These are pseudomorphic Ge/Ge1-ySny structures, SixGe1-x-ySny structures lattice matched to Ge and (partially) relaxed Ge1-ySny virtual substrates. The photonic devices consist of heterojunction diodes with vertical pin doping structures. As an example, Ge/Ge1-ySnymulti quantum well photodetectors which active regions made from Nx(Ge0.93Sn0.07/Ge) multi-quantum well structures are presented. Optical measurements at high frequencies are successfully performed on these photodetectors. A 3-dB bandwidth above 40 GHz is measured at the optical telecommunication wavelength of 1550 nm.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Germanium; Photodetector; Photonic device; Silicon; Silicon photonics; Tin